KOMPETENSI PEDAGOGIK GURU DALAM PELAKSANAAN PEMBELAJARAN TEMATIK KELAS IV DI SD NEGERI 01 SEPAUK KECAMATAN SEPAUK SINTANG - Herman Nganas; Luhur Wicaksono; Suciati Suciati (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
The teacher's pedagogic competence can be used to understand students well and be able to create an active and fun learning environment and the teacher is better able to manage the class so that student learning outcomes are at an optimal level. This research is a qualitative research. Data collection was carried out by observing, interviewing, documenting, and reinforced by the Likert scale of student perceptions in grade 4. Data analysis was carried out by data reduction, data presentation or data display, and data verification and drawing conclusions. The source of the data in this study were Class IV teachers at Sepauk 01 Public Elementary School, Sepauk District, Sintang Regency. Based on the conclusion, the class teacher in applying the teacher's pedagogic competence 1) has prepared a thematic learning design with the 2013 curriculum that the teacher made is appropriate; 2) has carried out all aspects of learning activities at the stage of implementing learning in accordance with the order and theories of thematic learning with the 2013 curriculum principles and directed at achieving Basic Competencies, Core Competencies, Indicators and learning objectives; 3) have carried out authentic assessments of assignments, written test results, homework, and presentation of assignment results and provided assessments of knowledge aspects, by assessing the results of discussions and individual work of students.